Assessment of size at first maturity for Ruditapes philippinarum from Arcachon Bay (French Atlantic coast): New insights for fishery management. (31st May 2023) - Caill-Milly, N.; Sanchez, F.; Benito, D.; Ruiz, P.; Izagirre, U.; Briaudeau, T.
Abstract: Regarding fisheries, management strategies aim at regulating access to the resource and at enforcing resource conservation in order to achieve sustainable exploitation. In this context, Minimum Conservation Reference Size (MCRS) is a technical measure based on scientific knowledge of the species characteristics (sexual maturity, individual growth and natural mortality). Reproductive capacity is generally apprehended by using the size at first maturity SL 50, the size at which 50% of the individuals are mature. The SL 50 was unknown for the Arcachon Bay Manila clam population ( Ruditapes philippinarum ). This study provides a first estimate based on the histological analysis of a large sample of individuals (1420 clams ranging from 10 to 41 mm) from four distinct bay inner sites and collected when the majority of the individuals are mature (from June to August). Our methodological choice was made to allow comparison with other European R. philippinarum deposits but also to be recognized by the EU; an interest of practices harmonization was besides revealed for bivalves. Following a logistic regression analysis, the SL 50 was estimated to be 26.7 mm for the totality of the samples considered, with moderate spatial variability. If only sexed individuals were taken into account in the estimation, the SL 50 was 24.5 mm for females and 21.6 mm for males. All sites and hypsometric levels combined, it is estimated that SL 50 is reached at an average age of 1.6 years, 32 mm at 2.3 years and 35 mm at 2.9 years with high variability at the scale of site-hypsometric level pairs. Considering the SL 50 and the spawning activity usually observed intra-basin, at least half of the clam population would have spawned at least once before their potential catch if the MCRS was reduced from 35 mm (current regulations) to 32 mm (regulations under study). This information constitutes essential knowledge to be included in Joint Recommendations when considering a MCRS revision in a European context that recognizes a more important place dedicated to regionalization. Highlights: SL 50 was determined for R. philippinarum based on gonad histology and logistic regression analysis. SL 50 is an essential parameter to assess the sustainability of a MCRS. Current MCRS (35 mm) is 29–34% higher that the estimated size at first maturity. Practices for histological analysis of bivalves reproduction would need to be harmonized.